1989
DOI: 10.1584/jpestics.14.351
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal Activity of Aliphatic Aldehyde and Ketone Pyrimidinylhydrazones

Abstract: The research program leading to the discovery of the agricultural fungicide ferimzone (proposed common name) was triggered by the interesting fungicidal activity of pyrimidinylhydrazones observed in our random fungicidal screening.Ferimzone, (Z)-2'-methylacetophenone 4, 6-dimethyl-2-pyrimidinylhydrazone, is a new fungicide with curative activity. It acts against rice blast, leaf spot and sheath blight by foliar treatment.A possibility of substitution of any aliphatic moiety for the aromatic moiety in ferimzone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Many microbial secondary metabolites were used for the control of plant diseases caused by R. solani 17,18 , H. sigmoideum 19,20 , and M. grisea [21][22][23][24] . (2), have the potential to be developed as agricultural fungicides, and specifically as products for the treatment of phytopathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Many microbial secondary metabolites were used for the control of plant diseases caused by R. solani 17,18 , H. sigmoideum 19,20 , and M. grisea [21][22][23][24] . (2), have the potential to be developed as agricultural fungicides, and specifically as products for the treatment of phytopathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 2-pyrazolylpyrimidines should be classified into the same 2-pyrimidinylhydrazone category as those described in previous papers. [1][2][3][4][5] Based on the result of the present study, 4, 6-dimethyl-2-(3, 5 -dimethylpyrazolyl) pyrimidine 11 was chosen for field evaluation from the viewpoint of its efficacy and structural simplicity. The fungicidal results indicated that 11 was not comparable to ferimzone.…”
Section: Resultsmentioning
confidence: 99%
“…Vol Pyracarbolid can be synthesized by transformation of 2H-3,4-dihydro-6-methylpyran-5-carboxylic acid into the acid chloride and further reaction with aniline [83].…”
Section: Anilidesmentioning
confidence: 99%